2015
DOI: 10.1021/acs.jpcc.5b04739
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Electrochemistry: Exploring the Hydrogen Evolution Reaction on Carbon Nanotubes

Abstract: Density functional theory (DFT) was employed to investigate the hydrogen evolution reaction (HER) on pristine and nitrogen doped carbon nanotubes (CNTs) in acidic solution. As the reaction is an electrocatalytic surface reaction, an accurate description of HER requires performing simulations under constant electrode potential conditions. To this end, we examined HER at several electrode charges allowing us to determine grand canonical activation energies as a continuous function of electrode potential. By stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 69 publications
10
66
0
Order By: Relevance
“…14 By contrast, the number of studies [15][16][17][18] exploring HER on carbonbased materials remains scarce and there is no theory motivated consensus on, for example, which dopants contribute to HER activity. In this Letter, we consider pristine open-ended CNTs and demonstrate how the reactivity of carbon can be tuned by the formation of 5-ring structures.…”
mentioning
confidence: 99%
“…14 By contrast, the number of studies [15][16][17][18] exploring HER on carbonbased materials remains scarce and there is no theory motivated consensus on, for example, which dopants contribute to HER activity. In this Letter, we consider pristine open-ended CNTs and demonstrate how the reactivity of carbon can be tuned by the formation of 5-ring structures.…”
mentioning
confidence: 99%
“…Instead, the kinetics of these within electrochemical energy conversion highly relevant reactions have been investigated atomistically employing only static approaches. [27][28][29][30][31][32][33][34][35] This work presents a comparative study of the CI-NEB and constrained MD methodologies and their ability to describe the transition path and the associated potential energy surface of the Volmer-HeyrovskĂ˝ mechanism of HER. In acidic media, the Volmer-HeyrovskĂ˝ mechanism proceeds via two protoncoupled electron transfer (PCET) steps; (1) electrosorption of a solvated proton, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several experiments were performed to show the effects of the silicon precursor's amount, the order of introducing precursors and the effect of growth's temperature on the yields, structure and morphology of the product. Moreover, density functional theory calculations showed the catalytic potency for CNTs in the hydrogen evolution reaction (HER) . The reported studies showed that these materials could decrease the barriers and increase the potential (V) of this reaction when they employed as catalyst ,.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, density functional theory calculations showed the catalytic potency for CNTs in the hydrogen evolution reaction (HER). [19] The reported studies showed that these materials could decrease the barriers and increase the potential (V) of this reaction when they employed as catalyst. [20,21] In the published experimental study, the electrochemical behavior of CNTs as a catalyst of HER has been investigated.…”
Section: Introductionmentioning
confidence: 99%